TARIFF ELIMINATION: IMPACTS AND TREATMENTS FOR RESOLVING NIGERIA-EPAs STALEMATE - Onogwu, Godwin Odo; Bzugu, Peter Madu; C. Ani, Emmanuel (Journal of Developing Economies, 2019)
In this manuscript, attempts were made to assess the impacts on Nigeria of full and instant tariff elimination from agricultural imports. A schedule of annual percentage reductions till full elimination as against an instant total or arbitrary elimination across all imports from the EU, as well asthe expected annual provisions via aids for envisaged trade to install infrastructural capacity aimed at forestalling fiscal imbalance, leading to stabilization for Nigeria, advocated. The study evaluates the likely share of Nigeria's imports from the European Union (EU), Economic Community of West African States(ECOWAS), and the rest of the world (ROW) in major agricultural product sections trade. The World Integrated Trade Solutions (WITs) platform was used to illicit a likely Economic Partnership Agreements (EPAs) scenario import data through a tariff eliminated query set up. The major impacts estimated include the resultant consumption impact, revenue impact, welfare impact, trade creation and diversion impacts, welfare impact of trade creation with consumption impact, and Welfare impacts of trade diversion with consumption impacts, in addition to their implications for scheduled tariff eliminations. Summary results were presented at product section levels as percentage of the impacts to contribution of agricultural sector in Nigeria's GDP. Based on the estimated impacts and terms of trade deal, it is recommended that Nigeria should follow a schedule of percentage tariff reduction across product sections relative to the current most favored nations' rather than arbitrary measures as a major policy of liberalizing trade. An annual percent tariff reduction rates over the 25 years, of 0.38%; 1.35%; 0.62%; 0.72%; and 0.2, for product sections 01-05, respectively, is recommended. In addition, it is also recommended that corresponding tariff losses in revenue due to scheduled reductions in tariff should be provided annually via aid for trade, for improvement in infrastructure, production and exportation that will sustain and improve intra, inter and extra regional trade in a growth and globalization pursuit aided by the EU. Keywords: International Agricultural Product Imports; Aid for Trade; EPAs; Impacts; Percentage Tariff Reduction Schedule.JEL Classification: F; F1; F6